Proteomic and Functional Analysis of the Effects of Quinoxaline Derivatives on Entamoeba histolytica - Avila-Bonilla, Rodolfo Gamaliel; López-Sandoval, Ángel; Soto-Sánchez, Jacqueline; Marchat, Laurence A.; Rivera, Gildardo; Medina-Contreras, Oscar; Ramírez-Moreno, Esther (Frontiers in Cellular and Infection Microbiology, 2022)
Quinoxalines are heterocyclic compounds that contain a benzene ring and a pyrazine ring. The oxidation of both nitrogen of the pyrazine ring results in quinoxaline derivatives (QdNO), which exhibit a variety of biological properties, including antiparasitic activity. However, its activity against Entamoeba histolytica, the protozoan that causes human amebiasis, is poorly understood. Recently, our group reported that various QdNOs produce morphological changes in E. histolytica trophozoites, increase reactive oxygen species, and inhibit thioredoxin reductase activity. Notably, T-001 and T-017 derivatives were among the QdNOs with the best activity. In order to contribute to the characterization of the antiamebic effect of QdNOs, in this work we analyzed the proteomic profile of E. histolytica trophozoites treated with the QdNOs T-001 and T-017, and the results were correlated with functional assays. A total number of 163 deregulated proteins were found in trophozoites treated with T-001, and 131 in those treated with T-017. A set of 21 overexpressed and 24 under-expressed proteins was identified, which were mainly related to cytoskeleton and intracellular traffic, nucleic acid transcription, translation and binding, and redox homeostasis. Furthermore, T-001 and T-017 modified the virulence of trophozoites, since they altered their erythrophagocytosis, migration, adhesion and cytolytic capacity. Our results show that in addition to alter reactive oxygen species, and thioredoxin reductase activity, T-001 and T-017 affect essential functions related to the actin cytoskeleton, which eventually affects E. histolytica virulence and survival.